Büyüme Modeli Bir Ön Çalışma, Durum Faktörü ve Yeni Kalaba River, Nijerya'da Sicklefin Kefali, Liza falcipinnis (Valenciennes, 1836) Nüfus Yapısı - Olopade, Olaniyi Alaba; Dıenye, Henry Eyina; Amponsah, Samuel Kweku Konney (Fırat University, 2019)
Nijerya'daki New Calabar Nehri'nden Sicklefin Mullet Liza falcipinnis Valenciennes 1836 nın büyüme modeli, durum faktörü ve stok özellikleri üzerine bir araştırma Ocak-Aralık 2017 arasında yapıldı. L. falcipinnis'in uzunluğu 9.1 ila 37.1 cm arasında değişirken ağırlık 13 ila 370 g olarak değişmektedir. Uzunluk ağırlık ilişkisinin sonucu negatif allometrik büyüme paternini değeri b=2.38 ve koşul faktörü (k)= 0.88 ile ortaya çıkarılmıştır. Asimptotik uzunluk (L?), büyüme katsayısı (K) ve büyüme performans endeksi (? - phi prime) sırasıyla 33.1 cm, yılda 0.18 ve yıllık 2.295 olarak hesaplandı. Araştırmada kaydedilen toplam doğal ve balıkçılık ölüm oranları sırasıyla yıllık 1.17, yıllık 0.56 ve yıllık 0.61 iken, kullanma oranı (E) değeri 0.52 olmuştur. Yakalama rutini olasılığının lojistik regresyonu 13,8 cm'de % 50 LC tahmini yapmıştır. İstihdam başına üretilen Emax değerlerini maksimuma çıkaran sömürü oranı 0,88 olup bu türlerin aşırı avlandığını göstermiştir. Tüm bu sonuçlar, çalışılan balık türlerinin sürdürülebilir kullanımı için New Calabar Nehri'ndeki balıkçılık faaliyetlerinin düzenlenmesi gerektiğini ortaya koymaktadır.

A study on growth pattern, condition factor and stock characteristics of the Sicklefin Mullet Liza falcipinnis Valenciennes, 1836 from the New Calabar River, Nigeria was undertaken from January to December 2017.  The length of L. falcipinnis ranged from 9.1 to 37.1 cm while weight was between 13 to 370 g. The result of length weight relationship revealed negative allometric growth pattern with the b value of 2.38 and condition factor (k) of 0.88. The asymptotic length (L?), growth coefficient (K) and index of growth performance (? – phi prime) were estimated at 33.1 cm, 0.18 per year and 2.295 per year respectively. The total, natural and fishing mortality rates recorded in the study were 1.17 per year, 0.56 per year and 0.61 per year respectively while the exploitation ratio (E) value was 0.52. The Logistic regression of the probability of capture routine gave an estimate of LC 50% at 13.8 cm. The exploitation rate which maximises yield per recruit produced values of Emax was 0.88, which indicated that the species was overfished. All these results reveal the need to regulate fishing activities in the New Calabar River for sustainable exploitation of the studied fish species.
A Preliminary Study of Growth Pattern, Condition Factor and Population Structure of Sicklefin Mullet, Liza falcipinnis (Valenciennes, 1836) in the New Calabar River, Nigeria
Keywords: Engineering; Mühendislik